Media Coverage of Valentine’s Day: Is Media Biased in Covering the Festival? - Siddiqui, Taha (International Journal of Social Sciences and Management, 2016)
Valentine’s Day celebration in India has been much debated and covered by the media in the last couple of years. In the year 2009, far right Hindu activist from Sri Ram Sena to Bajrang Dal were involved in beating up unmarried couples and blackening their faces, as mark of shame for celebrating Valentine’s Day. They claimed that the festival was a “western practice” and promotes “lust not love”. Following this other Anti- Valentine’s Day groups also expressed their views and this led to public debate about moral policing and Indian culture. However what is interesting to note is the fact how media covered. At one side media has played a big role in promoting it (for many reasons) and on the other hand it has also criticized it for cultural and religious concerns. This research tries to explore in depth how media covers the festival with commercialization, culture, religion and politics in the backdrop. The research studies 9 newspapers of in 3 different languages, namely English, Hindi and Urdu. The study tries to find out whether media is biased in covering the festival or is it propagating an idea to its readers. The idea of taking 3 different languages is to draw a sharp comparison and contrast among the national and vernacular newspapers. In order to find it, both quantitative and qualitative methods have been applied to the articles. Content analysis and Textual analysis are the important methods used to find out the statistics and underlying meanings behind these articles. Int. J. Soc. Sc. Manage. Vol. 3, Issue-3: 171-187